2002
DOI: 10.1590/s0100-39842002000100008
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos Ultra-Sonográficos Da Esquistossomose Hepatoesplênica

Abstract: A ultra-sonografia representa uma importante contribuição no diagnóstico da forma hepatoesplênica da esquistossomose. A ultra-sonografia permite a identificação das principais alterações, como espessamento periportal, perivesicular, aumento do lobo hepático esquerdo, redução do lobo hepático direito e esplenomegalia. Adicionalmente, os padrões hemodinâmicos podem ser avaliados com o Doppler, sendo possível a análise das veias porta, mesentérica superior e esplênica, além de facilitar o estudo dos vasos venosos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…Finally, just as demonstrated by other authors (4) , the present study demonstrated that ultrasonography, besides being a lowcost, non-invasive and widely available imaging method, is highly sensitive and reproducible in the evaluation of splenic siderotic nodules in patients affected by schistosomal portal hypertension.…”
Section: Resultssupporting
confidence: 85%
“…Finally, just as demonstrated by other authors (4) , the present study demonstrated that ultrasonography, besides being a lowcost, non-invasive and widely available imaging method, is highly sensitive and reproducible in the evaluation of splenic siderotic nodules in patients affected by schistosomal portal hypertension.…”
Section: Resultssupporting
confidence: 85%
“…Probably because of the lack of a specific training for sonographists and also the uncertainties about the method reproducibility, the Niamey classification has not been underutilized. US examinations in schistosomotic patients, in our environment, have been restricted to the evaluation of portal and splenic veins, organometry, and fluxometry of portal vein (16) .…”
Section: Discussionmentioning
confidence: 99%
“…For the diagnosis of schistosomiasis, the criterion used was the positive epidemiology, hepatic/abdominal ultrasound with characteristic findings (periportal fibrosis, splenomegaly, left hepatic lobe enlargement) 15 or coproparasitological examination positive for schistosome eggs using the the KatoKatz method, confirmed by review of medical records 16 .…”
Section: Introductionmentioning
confidence: 99%